Perioperative caearean section pain management at Groote Schuur hospital ? an audit - Giles, Daniel (Department of Anaesthesia and Perioperative Medicine, 2025)
Background: Caesarean section is one of the commonest surgeries performed resulting in moderate-to-severe pain in a significant proportion of women. The PROSPECT (procedure specific postoperative pain management) group includes surgeons and anaesthetists who develop procedure-specific consensus recommendations on managing postoperative pain. Our audit compared current clinical practice to that recommended by the updated PROSPECT guidelines for caesarean section from 2020. Methods: A cross-sectional observational study was conducted using the PAIN OUT standard operating procedures. The data were collected between 11 February and 5 March 2022 and uploaded onto the PAIN OUT registry. The appropriate data were extracted and used to describe the current standard of care directly against each of the nine interventions recommended by the PROSPECT guidelines. Results: A total of 84 patients were included in the audit. Five of the recommended interventions were not done at all (intrathecal long-acting opioid, preoperative oral paracetamol, intraoperative and postoperative NSAID, intraoperative intravenous dexamethasone), two intraoperative interventions were done poorly (intravenous paracetamol 15.5%, local anaesthetic 15.5%) and two postoperative interventions were done well (oral paracetamol 89.3%, intramuscular morphine 100%). Conclusion: Current clinical practice for the perioperative pain management of caesarean sections at this hospital falls short of best practice as outlined in the PROSPECT guidelines. The introduction of a perioperative protocol, and continuing education of doctors, nurses and patients on pain and its management may be effective ways to improve practice.